Archaeology of Champā and Vikramaśīlā - Prasad, Ram Chandra (Ramanand Vidya Bhawan, 1987)
Antiquities of Bhāgalpur District, Bihar; to 1200.
Keywords: Funde; Excavations (Archaeology) -- India -- Bhāgalpur (District); Archäologie; Indien; Bhāgalpur (India : District) -- Antiquities; Distrikt Bhagalpur; Hochschulschrift